SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN TINTER KACA FILM TERBAIK MENGGUNAKAN METODE ARAS (STUDI KASUS: PT. DEGREE THE AMBASSADOR) - Ayulia Sari; Nelly Astuti Hasibuan; Imam Saputra (STMIK Budi Darma, 2019)
Tinter is the person in charge of installing window film on building windows or car windows. A tinter must have some specific criteria set by the company. To increase motivation and quality of a tinter's work, the company routinely holds the selection of the best tinter each year. However, the selection of the best tinter made at this time is still not completely in accordance with the specified criteria and in the end the selection is based on the assessment of the company's leadership. It is feared that it will cause divisions between tinter who feel that the selection is unfair or not objective and does not conform to procedures. For this reason, a decision support system is needed for the selection of the best tinter. Decision support system used is to use the Additive Ratio Assessment (ARAS) method because this method is a multi criteria decision making method based on the ranking concept.Keywords : Tinter, System, Decision, SPK, Additive Ratio Assessment, ARAS